Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
2017
DOI: 10.1016/j.bbagrm.2017.08.010
|View full text |Cite|
|
Sign up to set email alerts
|

Transcriptional and epigenetic analyses of the DMD locus reveal novel cis ‑acting DNA elements that govern muscle dystrophin expression

Abstract: The dystrophin gene (DMD) is the largest gene in the human genome, mapping on the Xp21 chromosome locus. It spans 2.2Mb and accounts for approximately 0,1% of the entire human genome. Mutations in this gene cause Duchenne and Becker Muscular Dystrophy, X-linked Dilated Cardiomyopathy, and other milder muscle phenotypes. Beside the remarkable number of reports describing dystrophin gene expression and the pathogenic consequences of the gene mutations in dystrophinopathies, the full scenario of the DMD transcrip… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 9 publications
(5 citation statements)
references
References 34 publications
0
5
0
Order By: Relevance
“…inhibitor GSK126 [49] abolished Gm12794c repressive effects demonstrating that functional PRC2 complex is required for the Gm12794c-mediated p21/Cdkn1A transcriptional repression (Fig. 5c).…”
Section: Gm12794c-dependent Inhibition Of P21/cdkn1a Transcription Inmentioning
confidence: 85%
“…inhibitor GSK126 [49] abolished Gm12794c repressive effects demonstrating that functional PRC2 complex is required for the Gm12794c-mediated p21/Cdkn1A transcriptional repression (Fig. 5c).…”
Section: Gm12794c-dependent Inhibition Of P21/cdkn1a Transcription Inmentioning
confidence: 85%
“…RNA pol II can enter a paused or stalled status immediately downstream of the transcription start site before productive elongation occurs. Therefore, we suggested that this region is crucial for dystrophin transcriptional dynamics 23 .…”
Section: Discussionmentioning
confidence: 93%
“…Interestingly, we found differences in DMD cells depending on mutations. DMD patients’ cells carrying a deletion which includes exon 52 showed a very reduced DMD transcript, possibly related to the role of intron 52 regions in the chromatin shape which regulates DMD transcription 23 . Indeed, we previously reported a unique pausing site of RNA pol II in intron 52, which is almost invariably the site of breakpoint in exon 52 deletions.…”
Section: Discussionmentioning
confidence: 99%
“…Very little is known about DMD locus epigenetics. A few studies demonstrated the presence of regions of open chromatin structures, which may have still unravelled regulatory roles [15] . Finally, it should not be forgotten that the DMD gene is an onco-suppressor gene, acting either in myogenic cancers but also in brain cancer types [16] .…”
Section: Dystrophin Gene Regulation and Protein Expression In The Hummentioning
confidence: 99%